Fully reversible three-state interconversion of metallosupramolecular architectures. Issue 56 (24th June 2016) - Mittal, Nikita; Saha, Manik Lal; Schmittel, Michael
Abstract : The reversible switching of a sterically encumbered phenanthroline–Cu + –picolinaldehyde trio back and forth between homoleptic and heteroleptic coordination using the relative metal-ion to ligand ratio is the basis for an unprecedented cyclic three-state interconversion of metallacycles. Abstract : The reversible switching of a sterically encumbered phenanthroline–Cu + –picolinaldehyde trio back and forth between homoleptic and heteroleptic coordination using the relative metal-ion to ligand ratio is the basis for an unprecedented cyclic three-state interconversion of metallacycles.